2015
DOI: 10.3324/haematol.2014.118463
|View full text |Cite
|
Sign up to set email alerts
|

CD133 marks a stem cell population that drives human primary myelofibrosis

Abstract: MethodsPatients with primary myelofibrosis, normal donor specimens and study approval

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
(46 reference statements)
2
10
0
Order By: Relevance
“…Based on prior work there are several proteins including CD133, CD90 and CD24 which may be good markers of PanINs. CD133 is a marker for many stem cells which has been used to identify putative CSC from solid tumors [ 25 27 ]. Kazuya S et al reported that CD133 staining was not observed in all stages of PanIN or IPMN and only expressed in PDAC, which indicates that it can differentiate IPMN from PDAC but not PanIN from IPMN [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior work there are several proteins including CD133, CD90 and CD24 which may be good markers of PanINs. CD133 is a marker for many stem cells which has been used to identify putative CSC from solid tumors [ 25 27 ]. Kazuya S et al reported that CD133 staining was not observed in all stages of PanIN or IPMN and only expressed in PDAC, which indicates that it can differentiate IPMN from PDAC but not PanIN from IPMN [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular mechanisms and other clues suggest the clonal nature of the disease and that mutational clonal evolution in PMF is dependent on multiple hematopoietic clones [ 22 24 ]. The pathological hematopoietic stem cells harbor genetic mutations conferring the proliferative phenotype of the disease.…”
Section: Myeloproliferation and Myelofibrosis: The Dual Complementmentioning
confidence: 99%
“…Mutations can also occur in epigenetic regulator genes such as TET-2 [ 37 ], DNMT3A [ 38 ], or ASXL1 [ 39 ]. Recently, stem cell populations from PMF patients identified by the expression of CD133 have been investigated and after transplantation into mice were able to recapitulate major PMF parameters, revealing that CD133 marks a stem cell population that drives PMF [ 24 ]. However, despite numerous mutations, none are able, as the BCR-ABL mutations in chronic myeloid leukemia, to fully recapitulate the disease in an animal model or to entirely explain the pathophysiological features of PMF.…”
Section: Myeloproliferation and Myelofibrosis: The Dual Complementmentioning
confidence: 99%
“…Hypoxia activated HIF-1α/Twist-Bmi1 axis promote epithelial-mesenchymal transition (EMT) and renal fibrogenesis22. CD133-positive cells could drive chronic and acute phases of primary myelofibrosis in mice23. Sox2-positive skin progenitor cells were found to contribute to bleomycin-induced skin fibrosis24.…”
Section: Discussionmentioning
confidence: 99%